Factors Indicative of Recurrence Paraumbilical Hernia: Experience at a Tertiary Care Hospital in Dhaka City - Khalil, Mohammad Ibrahim; Saha, Haridas; Islam, Aminul; Mamun, Abdullah Al; Hossain, AZM Mostaque; Mahmud, Shahabuddin (Journal of Current and Advance Medical Research, 2018)
Background: Paraumbilical hernia has gained little attention from surgeons in comparison with other types of abdominal wall hernias (inguinal, postoperative); however, the primary suture for paraumbilical hernia is associated with a recurrence rate of 19.0 to 54.0%. Objective: The aim of this study was to analyze the results of the paraumbilical hernia repair and to assess the independent risk factors influencing paraumbilical hernia recurrence. Methodology: A retrospective analysis of patients who underwent surgery for paraumbilical hernia in the department of surgery, Dhaka Medical College Hospital from 2012 to 2015 was performed. Age, sex, hospital stay, hernia size, patient’s body mass index, and postoperative complications were analyzed. Postoperative evaluation included pain and discomfort in the abdomen and hernia recurrence rate. Hernia recurrence was diagnosed during the patients’ visit to a surgeon. Two surgical methods were used to repair paraumbilical hernia: open suture repair technique (keel technique) and open mesh repair technique (onlay technique). Every operation was chosen individually by the surgeon. Results: Ninety-seven patients (31 males and 66 females) with paraumbilical hernia were examined. The rate of postoperative complications was 5.2%. The complete patient’s recovery time after surgery was 2.4±3.4 months. Fourteen patients (20.9%) complained of pain or discomfort in the abdomen, and 7(10.4%) patients had ligature fistula after the surgery. Forty-five patients (67.2%) did not have any complaints after surgery. The recurrence rate after paraumbilical hernia repair was 8.9%. The recurrence rate was higher when hernia size was >2cm (9% for <2 cm vs 10.5% for >2 cm) and patient’s BMI was >30 kg/m2 (8.6% for <30 vs 10.7% for >30). Conclusion: In conclusion significant independent risk factors are found for paraumbilical hernia recurrence. Journal of Current and Advance Medical Research 2018;5(1):11-14